PERKEMBANGAN HUKUM WARIS ADAT SIMALUNGUN DALAM PEMBAGIAN WARISAN TERHADAP ANAK PEREMPUAN (STUDI DI KECAMATAN PEMATANG RAYA KABUPATEN SIMALUNGUN) - AIDA SIMARMATA (PREMISE LAW JURNAL, 2017)
The traditional inheritance law in Indonesia is much influenced by the kinship applied by the ethnic community, including in determining beneficiary of the part bequeathed. Simalungun Traditional Inheritance Law like other Batak Traditional Inheritance Law in general gives priority to a son as the main beneficiary. It is also applied by Simalungun Traditional Community who lives at Pematang Raya Subdistrict, Simalungun Regency. This has encouraged the conduct of this research. The results show that the inheritance distribution to daughters in Pematang Raya Subdistrict, Simalungun Regency has been developed. The factors that influence this development are parents’ affection, Religion, Education, Economy, and Social factors. Consequently, daughters receive the position as their parents’ beneficiaries; however, it does not mean that they can pass along their families’ names to the next generation or to replace sons’ position in the family. It is recommended that panatua adat and government hold counseling on inheritance distribution to daughters so that Simalungun Traditional community in Pematang Raya Subdistric have knowledge about it and give the chance to every daughter to pursue higher education, to join and to have a vote in the decision making in the tradition without underestimating of replacing the position of sons who pass along family’s name to the next generation. Keywords: Development, A Daughter’s Inheritance Right, Simalungun                     Tradition